Association between TyG index trajectory and new-onset lean NAFLD: a longitudinal study - Liu, Haoshuang; Chen, Jingfeng; Qin, Qian; Yan, Su; Wang, Youxiang; Li, Jiaoyan; Ding, Suying (Frontiers in Endocrinology, 2024)
The purpose of this manuscript is to identify longitudinal trajectories of changes in TyG index and investigate the association of TyG index trajectories with risk of lean NAFLD. Using data from 1,109 participants in the Health Management Cohort longitudinal study, we used LCGM to develop TyG index trajectories. Using a Cox proportional hazard model, the relationship between TyG index trajectories and incident lean NAFLD was analyzed. RCS were used to visually display the dose-response association between TyG index and lean NAFLD. We also deployed ML via LightGBM to predict lean NAFLD, validated by ROCs. The LightGBM model was used to create an online tool for medical use. In addition, NAFLD was assessed by abdominal ultrasound after excluding other liver fat causes.The median age of the population was 46.6 years, and 440 (39.68%) of the participants were men. Three distinct TyG index trajectories were identified: "low stable" (TyG index ranged from 7.66 to 7.71, n=206, 18.5%), "moderate stable" (TyG index ranged from 8.11 to 8.15, n=542, 48.8%), and "high stable" (TyG index ranged from 8.61 to 8.67, n=363, 32.7%). Using a "low stable" trajectory as a reference, a "high stable" trajectory was associated with an increased risk of lean-NAFLD (HR: 2.668, 95% CI: 1.098-6.484). After adjusting for baseline age, WC, SBP, BMI, and ALT, HR increased slightly in "moderate stable" and "high stable" trajectories to 1.767 (95% CI:0.730-4.275) and 2.668 (95% CI:1.098-6.484), respectively. RCS analysis showed a significant nonlinear dose-response relationship between TyG index and lean NAFLD risk ( 2 =11.5, P=0.003). The LightGBM model demonstrated high accuracy (Train AUC 0.870, Test AUC 0.766). An online tool based on our model was developed to assist clinicians in assessing lean NAFLD risk.The TyG index serves as a promising noninvasive marker for lean NAFLD, with significant implications for clinical practice and public health policy. NAFLD can occur in lean individuals and is often associated with low awareness in the general population.  Patients with lean NAFLD have worse outcomes than the general NAFLD population. 4  Development of newer marker targets for lean NAFLD patients for use in future trials.